2012
DOI: 10.1093/humupd/dms006
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyosis and subfertility: a systematic review of prevalence, diagnosis, treatment and fertility outcomes

Abstract: Further studies are needed to determine the natural history of adenomyosis and implications for fertility and reproductive outcomes, with and without treatment. Currently, there is no evidence that we should find and treat adenomyosis in patients who wish to conceive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(146 citation statements)
references
References 50 publications
(54 reference statements)
2
128
2
8
Order By: Relevance
“…The pathological process of EM comprises periodic bleeding, migration of uterine cells and their attachment to other organs. In general, EM is only seen in women of childbearing age, mostly at the age of 25-45 years (3,4). The major symptoms of the disease are dysmenorrhea, chronic pelvic pain and infertility that seriously affect the quality of life of young women (5).…”
Section: Introductionmentioning
confidence: 99%
“…The pathological process of EM comprises periodic bleeding, migration of uterine cells and their attachment to other organs. In general, EM is only seen in women of childbearing age, mostly at the age of 25-45 years (3,4). The major symptoms of the disease are dysmenorrhea, chronic pelvic pain and infertility that seriously affect the quality of life of young women (5).…”
Section: Introductionmentioning
confidence: 99%
“…Costello et al [3 ]reported that the presence of adenomyosis did not adversely affect the outcome in women undergoing in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) treatment. The most recent systematic review of five existing studies failed to draw any definite conclusions about the effect of adenomyosis on the outcomes of assisted reproductive technology because of major differences in study design and populations [4]. …”
Section: Introductionmentioning
confidence: 99%
“…планируют сохранить свою фертильность, а чаще всего еще даже не реализовали свой репродуктивный потенциал [9,10].…”
Section: Abstract: Adenomyosis Myoma Uteri Hormone Therapy Osada Ounclassified